2016
DOI: 10.1021/acsami.5b12688
|View full text |Cite
|
Sign up to set email alerts
|

Selective Antimicrobial Activities and Action Mechanism of Micelles Self-Assembled by Cationic Oligomeric Surfactants

Abstract: This work reports that cationic micelles formed by cationic trimeric, tetrameric, and hexameric surfactants bearing amide moieties in spacers can efficiently kill Gram-negative E. coli with a very low minimum inhibitory concentration (1.70-0.93 μM), and do not cause obvious toxicity to mammalian cells at the concentrations used. With the increase of the oligomerization degree, the antibacterial activity of the oligomeric surfactants increases, i.e., hexameric surfactant > tetrameric surfactant > trimeric surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
153
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 50 publications
(113 reference statements)
4
153
0
1
Order By: Relevance
“…6 The lowest observed effective concentration of cetylpyridinium chloride (CPC) was 1.5 mM. 56 The limit of detection (LOD) using 2,5-DHB and CTS@Fe 3 O 4 MNPs is 200 fmole and 50 fmole, respectively.…”
Section: Sensitivity Of Cts@fe 3 O 4 Mnps For Cationic and Anionic Sumentioning
confidence: 99%
See 1 more Smart Citation
“…6 The lowest observed effective concentration of cetylpyridinium chloride (CPC) was 1.5 mM. 56 The limit of detection (LOD) using 2,5-DHB and CTS@Fe 3 O 4 MNPs is 200 fmole and 50 fmole, respectively.…”
Section: Sensitivity Of Cts@fe 3 O 4 Mnps For Cationic and Anionic Sumentioning
confidence: 99%
“…3 Surfactants interact with DNA, 4 humic acids, 5 the outer membrane of bacterial cells 6 and other biomolecules. It was reported that the ecotoxicity of hospital wastewater identied detergents and disinfectants as the main causes of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are an example of quaternary ammonium compounds. Synthesized and hexameric, tetrameric, and trimeric surfactants have been used recently to disrupt the outer membrane integrity of Escherichia coli and Staphylococcus aureus . The proposed mechanism of surfactants interaction with PA‐ OM is primarily based on the disruption of the integrity of PA‐ OM by electrostatic interaction between cationic ammonium groups of the surfactants and anionic groups of the LPS of PA, which undermines the barrier function of the outer layer .…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized and hexameric, tetrameric, and trimeric surfactants have been used recently to disrupt the outer membrane integrity of Escherichia coli and Staphylococcus aureus . The proposed mechanism of surfactants interaction with PA‐ OM is primarily based on the disruption of the integrity of PA‐ OM by electrostatic interaction between cationic ammonium groups of the surfactants and anionic groups of the LPS of PA, which undermines the barrier function of the outer layer . Moreover, these surfactants also contain long hydrophobic alkyl chains which enable further interaction with the hydrophobic lipid membrane or phospholipids, resulting in the disruption of the cellular membrane.…”
Section: Introductionmentioning
confidence: 99%
“…由此可知, 星 状寡聚表面活性剂可以通过调节分子构象来构筑不同 的聚集体结构. 我们的进一步研究表明星状寡聚表面活 性剂在许多方面表现出非常优异的性能: 三聚 DTAD、 四聚 PATC 和六聚 PAHB 阳离子季铵盐表面活性剂均表 现出优异的抗菌活性, 在最小抑菌浓度时无明显细胞毒 性, 并且这三种寡聚表面活性剂的抗菌活性随着寡聚度 的增加而增强 [21] ; 环糊精的加入能够在保持 DTAD 高效 抗菌活性的同时, 显著提高 DTAD 的温和性 [22] ; 六聚 PAHB 在极低浓度条件下形成网状聚集体的性质使其对 直链烷烃表现出很强的乳化能力 [19] . 总之, 星状寡聚表 [25] .…”
unclassified